Pengaruh Kompetensi Karyawan, Motivasi Kerja, dan Kepuasan Kerja Terhadap Kinerja Sistem Informasi Akuntansi di LPD - Putu Ardia Cahayanti; I Ketut Yadnyana (International Journal of Economics, Management and Accounting, 2024)
The development and progress of Village Credit Institutions (LPD) can be seen through various achievements such as financial performance and operational results. A good Village Credit Institution (LPD) is recognized from its financial reporting system and services. In reality, not all (LPD) are able to use AIS wisely and accurately. The purpose of this research is to understand the influence of employee competence, work motivation, and job satisfaction on the performance of the accounting information system. The population consists of LPDs in Ubud Regency, Bali with a representation of 96 people. The data collection techniques used in this study include quantitative. The studies that have been carried out prove that employee ability has a positive effect on AIS performance, work motivation has a positive effect on the use of AIS, and job satisfaction has a positive effect on the use of AIS. We found that it had a positive impact. The magnitude of the influence of independent variables on the use of AIS is 65.4%.